Managing Pandemic-induced Mental Health Concerns in the Philippines: A Strong Case for Building Public Trust and Confidence - Gaspar, Raymond E.; Dela Cruz, Nina Ashley O. (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2022)
Using an online survey among Filipinos jointly conducted by YouGov and the Institute of Global Health Innovation at the Imperial College London from 31 March to 30 September 2020, this paper examines the state of mental health in the Philippines during the height of the pandemic and its link to public trust in and confidence toward the government and relevant authorities. The analysis reveals that young adults, women, part-time employees, unemployed, and persons with comorbidities have faced elevated risks of psychological distress during the pandemic. Empirical results further indicate that having strong and capable governance, setting clear directions and guidelines, and effectively motivating compliant behaviors on safety protocols allay fears and concerns among these groups, and thus are instrumental to preventing potential cases of depressive and anxiety disorders.